Quality of Life in Schizophrenic Patients: The Relationship with Personal Characteristics - mohammed, Qahtan; Khudair, ali (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: The study aims to identify the quality of life level in schizophrenic patients and to find out therelationships between the quality of life and some of personal characteristics for those patients withschizophrenia.Methodology: A descriptive correlation analytic design was used by using the assessment technique on sampleof 100 schizophrenic outpatients, who were selected purposively (non-probability sample) during the period10/ 3/2013 - 1/ 12 /2013. The study was conducted on the schizophrenic patients in an out patient psychiatricclinics at Ibn-Rushd; and Al-Rashad Psychiatric Teaching Hospital; Baghdad Teaching Hospital, and Al-KadhimyaTeaching Hospital. Self administrative questionnaire was used which includes of two parts: the first includes thecovering letter and personal characteristics; the second include the quality of life scale (World HealthOrganization QoL-BREF). The validity of the instrument was determined by using of face validity through thepanel of experts, and the reliability of the instrument was determined by internal consistency through thecomputation of Alpha Correlation Coefficient (Cronbach's Alpha). The data were collected through theutilization of the self administrated questionnaire as a mean of data collection via structured interviewing. Dataanalysis was employed by applying the Statistical Package for Social Science version 17.0 (SPSS).Results: The results indicated that the majority of sample were single males aged from 30-44 years old whowere unemployed graduated from institute or college education. The higher percentage of them had 11 yearsand above duration of illness with 1-3 admission and complaining positive symptom. The majority ofschizophrenic patients have moderate quality of life level. There is a significant positive relationship betweenquality of life and marital status and there is no relationship with other characteristics.Recommendations: The study recommended of providing vocational and rehabilitative programs for theschizophrenic patients to improve their quality of life, and also the replication of the study with a large sampleis important.